Investments in Renewable Energy in Rural Communes: An Analysis of Regional Disparities in Poland - Agnieszka Kozera; Aldona Standar; Joanna Stanisławska; Anna Rosa (Energies)
Although energy transformation is a widely discussed topic, there is a dearth of research on the role of rural communes in implementing that concept in Poland, a country where rural areas account for more than 90% of the total landmass. Most research projects are focused on larger local government units, such as cities, whereas rural communes’ role in the development of local energy policies and impact on the development of renewable energy sources (RESs) is often disregarded. Therefore, this study extends the existing literature resources with a view to bridging that gap by assessing rural communes’ investment activity in the context of the Polish energy transformation, with particular emphasis on regional differences in RES investments financed with Union funds. Therefore, the main purpose of this study is to assess the contribution of rural communes to the Polish energy transformation process, with a particular focus on regional differences in renewable energy investments financed with European Union funds in the successive seven-year financial perspectives 2007–2013 and 2014–2020. The study aimed to answer the following key research questions: how does the level of rural communes’ investment activities related to renewable energy development compare to that of other commune types? What are the regional differences in rural communes’ investment activities related to renewable energy? What are the main factors affecting rural communes’ investment activity in regions most involved in the development of renewable energies? The study relies on data from the Ministry of Development Funds and Regional Policy and from the Local Data Bank of the Central Statistical Office. The dataset was processed with the use of descriptive statistics methods and Ward’s method with a view to identifying regional patterns and conditions for the development of renewable energy investments. This study focuses on the investment activities of rural communes in Poland related to RESs financed with European Union funds. The empirical research results highlight rural municipalities’ crucial role in developing RES, emphasizing their high investment activity and significant regional differences. Municipalities from the eastern Polish provinces of Lublin and Podlasie have successfully secured EU funds for RES development. They have implemented numerous projects, primarily related to solar energy.